Congenital Zyka virus syndrome, motherhood and experiences (Research, Society and Development, 2022)
Zika virus infection in pregnant women has been associated with microcephaly in newborns, with the first cases reported in Maranhão in late 2015. In mid-2017, a service for interdisciplinary care for families of children was inaugurated in São Luís, Maranhão. with Congenital Zika Virus Syndrome (SCZV). This article describes the care offered in circuits of experiences in this Reference Service, which develops a method to favor the mother-infant bond, enabling a redefinition of motherhood. It was qualitative research with an autoethnographic nature, using documental research, participant observation and group interviews from Operative Groups as data collection. It was possible to observe the approach of these mothers to their children, where, based on circuits of experiences, an attempt was made to innovate the care process, allowing the family to take the lead in care. The systematized interventions allowed the exchange of experiences and the consolidation of learning, replacing and surpassing activities centered on attention to illnesses and focused on children's rehabilitation.